Cassiopea xamachana microbiome across anatomy, development, and geography. - Allison H Kerwin; Aki Ohdera; Juliet Bier; Devon Goodman; Marta Mammone; Victoria Sharp; Alesandra Echeandía; Mónica Medina (PLoS ONE)
The upside-down jellyfish holobiont, Cassiopea xamachana, is a useful model system for tri-partite interactions between the cnidarian host, the photosymbiont, and the bacterial microbiome. While the interaction between the host and photosymbiont has been well studied, less is understood of the associated bacterial community. To date, the bacterial microbiome of wild C. xamachana has remained largely uncharacterized. Thus, wild medusae (n=6) and larvae (n=3) were collected from two sites in the Florida Keys. Bacterial community composition was characterized via amplicon sequencing of the 16S rRNA gene V4 region. The medusa bacterial community was dominated by members of the Alphaproteobacteria and Gammaproteobacteria, while Planctomycetota, Actinomycetota, Bacteroidota, and Bacillota were also present, among others. Community composition was consistent between locations and across medusa structures (oral arm, bell, and gonad). The larval bacterial community clustered apart from the medusa community in beta diversity analysis and was characterized by the presence of several Pseudomonadota taxa that were not present in the medusa, including the Alteromonas, Pseudoalteromonas, and Thalassobius genera. A bacterial isolate library encompassing much of the amplicon sequencing diversity was also developed and tested via metabolic assays in a separate culture-dependent analysis of isolates from medusa bells, oral arms, and laplets. Most characteristics were not correlated with host sex or medusa structure, but gelatinase production was more common in laplet isolates, while lactose fermentation was more common in female oral arm isolates. The Endozoicomonas genus was dominant in both amplicon sequencing and in our isolate library, and was equally prevalent across all medusa structures and in both sexes. Understanding the bacterial component of the C. xamachana holobiont will allow us to further develop this important model cnidarian holobiont.